Omega-3 fatty acid supplementation and the insulin-like growth factor (igf) system in early pregnancy in pigs - Brazle, A.; Rathbun, Theresa J.; Johnson, B.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The IGF system of growth factors, receptors and binding proteins functions from early in pregnancy. Recent evidence indicates improved embryo survival in gilts fed supplemental omega-3 fatty acids beginning before conception. Here we report effects of supplementing a corn-soybean meal diet (control) with a marine source of protected omega-3 fatty acids (PFA, 1.5% of diet) on mRNA expression for IGF-I, IGF-II, IGF Binding Protein-3 (IGFBP-3) and IGFBP-5 in the porcine gravid uterus. The PFA (Gromage™) contained equal amounts of eicosapentanoic (EPA) and docosahexanoic (DHA) acids and replaced corn in the diet beginning when gilts were approximately 170 d old (n = 13/treat-ment). Gilts were artificially inseminated at approximately 205 d of age. Conceptus and endometrial samples were collected on d 11, 15, and 19 of gestation. All gilts were pregnant. In the conceptus, message for IGF-II and IGFBP-3 increased (P<0.001) from d 15 to d 19, while there was an increase (P < 0.001) in IGF-I and IGFBP-5 from d 11 to 15 and a decrease (P<0.001) to d 19. In the endometrium, message for IGF-I was stable over the interval, but message for IGF-II and IGFBP-5 were increased by d 15 and IGFBP-3 by d 19 (P<0.01). There were trends for omega-3 fatty acid supplementation to increase endometrial IGF-II (P = 0.09) and IGFBP-5 (P = 0.12) on d 15. In the d-19 conceptus, embryonic but not extraembryonic IGF-I mRNA tended to be greater (P = 0.13) for PFA compared to control gilts. During d 11 to 19 the conceptus is elongating, attaching to the uterus, and the embryonic disc is differentiating from a homogenous tissue to form the tissues and organs of the adult. One mechanism for omega-3 fatty acid effects in early pregnancy could involve epigenetic effects on mRNA expression for the IGF and IGFBP proteins.
Keywords: Swine; Reproduction; IGF; Omega-3 fatty acids